A novel method for a new electromagnetic‐induced ammonia synthesizer. (12th May 2020) - Chehade, Ghassan; Dincer, Ibrahim
Summary: Since the triple bond in a nitrogen molecule is considered to be one of the strongest bond to break, the ammonia synthesis under atmospheric pressure and mild temperature becomes a remarkably challenging problem. In the present research study, a novel method is introduced for electrochemical ammonia synthesis through integrating the reactor with the electromagnetic zero‐voltage switching (ZVS) device. The reactor is tested under an induced electromagnetic (EM) field in galvanostatic mode by varying the operating parameters that include temperature, flow rate, and current density. The experimental setup is designed and operated toward performing the electrochemical synthesis. The maximum Faradaic efficiency achieved with EM field is 4.5%, and the ammonia formation rate is found to be 1.21 × 10 −10 mol cm −2 s −1 at an applied constant current of 6.4 mA cm −2 and EM field of 49 mT. Furthermore, the experiments are extended to include the ammonia synthesis with and without EM field influence on the reaction; in which case, the reduction potential becomes 1.25 V with the presence of EM field, while it is 1.7 V without EM field when the applied current of 6.4 mA cm −2 is incorporated. This study demonstrates that the electrochemical ammonia synthesis, via nitrogen reduction, can be achieved spontaneously, which is beyond the classical approach for electrochemical ammonia synthesis. Abstract : Ammonia synthesis mechanism.